The Influence of Product Quality, Service Quality, and Price on Purchasing Decisions at Customers Bila Bakery - Nabila Firdausa; Reny Nadlifatin (Publikasi Indonesia, 2024)
Customer behavior is like something complex where in the process there are internal factors and external factors that can influence customers to determine purchase decisions. In this study, data will be collected on the food and beverage industry, namely Bila Bakery. There is a phenomenon that occurs in Bila Bakery in the form of a decline in sales after the pandemic. In fact, in this case, If the bakery has data related to customer membership but has never been eval_uated, so the data cannot provide consideration in decision-making by management. This study is a quantitative research that uses a descriptive analysis method and PLS-SEM using data obtained from Bila Bakery customers through the distribution of questionnaires with WhatsApp Blast, there are 157 respondents as a sample in this study. The results of the study show that Product Quality and Price have a positive and significant effect on Purchase Decisions, but Service Quality has a positive effect but does not have a significant effect on Purchase Decisions on Bila Bakery customers. There are managerial implications for Bila Bakery as a future business strategy through Product Quality and Price that have an impact on Purchase Decisions.